P03 Explaining the decline in coronary heart disease mortality in Northern Ireland between 1987 and 2007. (16th November 2010) - Hughes, J; Kee, F; Bennett, K; O'Flaherty, M; Critchley, J; Capewell, S
Abstract : Purpose: In 1987, Northern Ireland had one of the highest rates of coronary heart disease (CHD) mortality in the world. However, CHD mortality has declined substantially over the last 2 decades. The purpose of this study is to determine the contribution of changes in CHD risk factors to CHD mortality decline from 1987 to to 2007. Methods: The validated IMPACT CHD mortality model was used in all calculations. We included data describing population size, CHD mortality and risk factor trends in adults aged 25–84 years old between 1987 and 2007. Regression coefficients and RR from the published literature quantified the relationship between population changes for a specific CHD risk factor (ie, smoking, diabetes, systolic blood pressure, total cholesterol, physical inactivity and obesity) and CHD mortality. The outcome of interest was the number of deaths prevented or postponed (DPPs) associated with changes in each specific CHD risk factor. Sensitivity analysis was applied to these estimates. Results: Preliminary results from 1987 to to 2007 indicate that the overall age-standardised CHD mortality rate in Northern Ireland (age 25–84 years) fell from 361 to 124 deaths per 100 000 inhabitants, resulting in an estimated 3180 fewer CHD deaths in 2007. Changes in CHD risk factors produced a total of 2090 fewer CHD deaths (minimum estimate 1410; maximum estimate 2820) in Northern Ireland. These reductions therefore accounted for approximately 65% of the total decrease in CHD mortality. The largest effect came from the substantial fall in total cholesterol (explaining approximately 40% of the reduction in CHD mortality), followed by reductions in smoking (24%) and population systolic blood pressure (17%). However, increases in some risk factors had a negative effect, actually increasing CHD mortality: diabetes prevalence (−9%), physical inactivity (−5%) and BMI (−2%). Research is currently underway to estimate the additional contribution of improved treatment uptake and effectiveness to the reductions in CHD mortality. Conclusions: Approximately two thirds of the recent large fall in CHD mortality in Northern Ireland between 1997 and 2007 was attributable to reductions in major cardiovascular risk factors. However, adverse trends in diabetes, obesity and physical inactivity are of major concern. More aggressive policies to promote healthy food and increase physical activity may therefore be needed to decrease future CHD deaths.